Regeneração e multiplicação in vitro de Caçari (Myrciaria dubia (kunth) McVaugh) - Ribeiro, Maria Isabel Garcia (2016)
The caçari is a native fruit from Amazonian, has great potential due to the high ascorbic acid concentrations up to 8,000 mg / 100 g pulp, currently being considered the richest fruit in vitamin C. However, being a native fruit, little is known about the vegetative propagation characteristics on a commercial scale. Among the vegetative propagation techniques, micropropagation stands out as one of the most promising techniques for commercial spread on a large scale and short time. In this sense, the purpose of this study was to evaluate the influence of the consistency of the medium, commercial fertilizer concentrations, Fe and cytokinin in the regeneration and proliferation in vitro of caçari. For this, two experiments were installed: 1) In vitro regeneration of caçari (Myrciaria dubia (Kunth). McVaugh) in culture medium containing different concentrations of commercial fertilizer and iron; 2) In vitro multiplication of caçari (Myrciaria dubia (Kunth.) McVaugh) with different concentrations of cytokinins. The experiments were conducted at the Embrapa Roraima Tissue Culture Laboratory and were used as explants shoot segments of caçari from mother plants grown in a greenhouse. After sterilization, explants were inoculated into 125 mm test tubes and 30 ml of WPM media. After inoculation, the explants remained for 15 days in the dark and then were transferred to a growth room with 16 hours of photoperiod, temperature 25 ± 2 °C and light 32μmol.m-2.s-1. After 90 days, the variable number of shoots, length of shoots and oxidation percentage were evaluated. For both experiments, the experimental design was completely randomized in a factorial with five replications, each replication consisted of five explants. In the first experiment, it was found that the addition of Maxsol® fertilizer at a dose of 0.75 g.L-1 in the culture medium promotes better healing of caçari shoots. The medium without addition of iron culture, provides better performance for the establishment of explants caçari. The iron in the regeneration phase of the explants caçari shown not essential and their presence does not contribute to the reduction of the oxidation process. In the second, it was found that most caçari proliferation of shoots is obtained with BAP at concentration of 4.9 mg.L-1. The addition of cytokinin in the culture medium was not beneficial to the length of sprouts. Tested cytokinins concentrations caused high oxidative effect, indicating the need to test lower concentrations.